Preliminary Analysis of the Impact of Finishing Layers on the Hygroscopic Performance of Vernacular Earthen Plasters from Santiago, Chile - Patrícia Marchante; Amanda Rivera Vidal; Simone Murgia; Antonia Navarro Ezquerra; Maddalena Achenza; Paulina Faria (Buildings)
Buildings of historic neighborhoods of Santiago de Chile are protected by a coating system composed of different layers of earth-based mortars, as part of a building culture that has been neglected and forgotten since the introduction of industrialized materials but still exists in many buildings. This study presents preliminary results from ongoing research that explores the hygroscopic capacity of this vernacular coating system and the impact of incorporating recent finishing layers into traditional construction practices. The investigation focuses on identifying materials and techniques typical of traditional Chilean coatings, highlighting their role in enhancing the durability of historic buildings, improving user comfort, and promoting environmental sustainability. It contributes to the conservation of historic buildings and their reuse, as well as to the health of its inhabitants, due to its contribution to hygrometric regulation. This article focuses on this last purpose, through the identification and characterization of the coating system and its finishing layer materials, and a comparative sorption/desorption test of four case studies with these vernacular coatings. This study began with the sample extraction in situ, followed by its observation and cataloguing. Stratigraphic and stereo microscope analysis of the finishing layers were carried out to identify them. The characterization of the finishing materials was performed using FTIR-ATR and SEM-EDX tests. The sorption/desorption test was performed with a set of original complete samples of the four case studies. Subsequently, another set was prepared with the removal of the finishing layers in order to compare their influence on the hygroscopicity of the coating systems. The results elucidate the variety of materials employed on the finishing layer of these coatings, which are often superimposed, revealing renovations and reparations over time. The influence of these finishing materials on sorption properties of the coating system (the scratch and base coats) is exposed by comparing the samples with and without them.